Development of a geomechatronic complex for the geotechnical monitoring of the contour of a mine working - Zaichenko, Stefan; Shalenko, Vadym; Shevchuk, Nataliia; Vapnichna, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2017)
While receiving information under dangerous conditions, at which human presence is difficult or impossible, widely spread are the mobile robotic complexes. Particularly important information to determine the stressed-strained state of the underground workings is data on their geometry. Establishing the values of convergence of underground workings will make it possible to locate dangerous areas and decrease the number of emergency cases. In order to design an experimental sample, we developed basic approaches to create geomechatronic complexes, which define the main tasks, the scope of application, and quality criteria. The motion of the complex along an underground working is accompanied by a spatial change in the position of a distance sensor, which must be considered when establishing the actual values of the profile of a working. As parameters that take into account a change in the position, we proposed six components, three displacements and three Euler angles, which are registered by a microelectronic gyroscope that registers the distance traveled. The proposed algorithm is a cyclical structure, which successively performs data registration from different sensors that define its position, data conversion, and data recording to a memory card. Implementation of the devised algorithm allows us to determine the geometry of a profile of the working with an accuracy of 0.5 cm.